Editorial for the Special Issue: Advances in the Biology of Phototrophic Bacteria - Johannes F. Imhoff (Microorganisms, 2021)
Phototrophic bacteria represent a very ancient phylogenetic and highly diverse metabolic type of bacteria that diverged early into several major phylogenetic lineages with quite different properties [...]